Laws of Evidence In The Resolution of State Administrative Disputes and Criminal Cases - Zendrato, Ferawati (SEAN Institute, 2025)
In every dispute/case process that is resolved through the courts, evidence is basically needed, whether it occurs in the process of resolving state administrative disputes, civil cases, and criminal cases. The Law of Evidence in procedural law is very important because the task of evidence determines the truth in a conflict of interest. And on the basis of this evidence, the judge makes a decision to try to find the truth. The law of evidence in state administrative procedural law, criminal law which has a different object of dispute where in the process of resolving disputes/cases there are similarities and there are differences in the principles adopted. One of the similarities in the principles adopted, in the resolution of state administrative disputes/in state administrative court procedural law there is the principle of presumption of rechtmatieg which has the same meaning as the presumption of innocence in criminal procedural law. In making a decision by a judge after examining the evidence, there is a difference between a state administrative court judge in resolving state administrative disputes and a district court judge in resolving criminal cases. In administrative disputes, a judge may make a decision based on a minimum of two pieces of evidence according to the judge's belief and there is no absolute evidence, while in criminal cases, the judge's decision must have sufficient evidence according to the law, there must be witness testimony and the judge's belief.